2020
DOI: 10.1093/europace/euaa284
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences of fatty acid-binding protein 4 and leptin levels in atrial fibrillation

Abstract: Aims Adiposity plays a key role in the pathogenesis of atrial fibrillation (AF). Our aim was to study the sex differences in adipokines levels according to AF burden. Methods and results Two independent cohorts of patients were studied: (i) consecutive patients with AF undergoing catheter ablation (n = 217) and (ii) a control group (n = 105). (i) Adipokines, oxidative stress, indirect autonomic markers, and leucocytes mRNA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Although the exact mechanisms remain elusive, clinical investigations have indicated sexual dimorphism in AF. Consistent with this rationale, in our previous study we have found an association between higher levels of FABP-4 in women with AF compared to men [ 8 ]. Recently, Ruben R. De With et al have shown that FABP4 levels were higher in women than in men with paroxysmal AF [ 22 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although the exact mechanisms remain elusive, clinical investigations have indicated sexual dimorphism in AF. Consistent with this rationale, in our previous study we have found an association between higher levels of FABP-4 in women with AF compared to men [ 8 ]. Recently, Ruben R. De With et al have shown that FABP4 levels were higher in women than in men with paroxysmal AF [ 22 ].…”
Section: Discussionsupporting
confidence: 78%
“…Leptin, an anorexic hormone released by adipocytes, regulates the pathogenesis of atrial fibrosis evoked by angiotensin II. Both adipokines are co-regulated during the inflammatory process of adipose tissue [ 7 ], and, interestingly, the plasma levels of both proteins differ between men and women depending on AF burden [ 8 ]. At present, conflicting evidence exists regarding the utility of biomarkers in detecting atrial cardiomyopathy as well as their role in predicting arrhythmia recurrence after AF ablation.…”
Section: Introductionmentioning
confidence: 99%
“… 13 López-Canoa et al . 14 have shown an association between higher levels of FABP-4 in women with AF in comparison to men, as well as recurrence of AF after ablation in both sexes. In contrast to what we found, Magnussen et al .…”
Section: Discussionmentioning
confidence: 96%
“…The information on the sex-differences in FABP4 expression is limited to circulating FABP4 levels. Results from the clinical studies showed an increased FABP4 plasma level in the female gender in several pathological conditions such as coronary atherosclerosis [ 19 ] or atrial fibrillation [ 18 ]. Conversely, in patients with stable angina and chronic kidney disease, male sex was associated with higher plasma FABP4 levels [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sex-differences in FABP4 expression is still a matter of debate. Women with atrial fibrillation [ 18 ] or coronary atherosclerosis [ 19 ] present higher plasma FABP4 levels, whereas women with stable angina and chronic kidney disease exhibit reduced plasma FABP4 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%